ANALYSING THE EFFECT OF USING ASSURE LEARNING MODEL ON THE DEVELOPMENT OF STUDENTS' LEARNING MOTIVATION - Aldin Gunawan Zai; Suderman Halawa; Ridoy Susanto Waruwu (CV. Fahr Publishing, 2023)
Using learning models appropriately has a big impact on the implementation of learning. This research aims to analyze the influence of the Assure learning model on the development of student learning motivation. This research includes descriptive qualitative research conducted using a systematic review or literature study method to obtain research discussion data. Articles in the analysis were selected based on certain criteria according to the keywords determined in the research. The findings show that all the articles analyzed (6 articles) support that the use of the Assure learning model has a positive influence on the development of student learning motivation. There is an increase in student learning outcomes from implementing the Assure learning model because with this learning model a learning atmosphere will be created that encourages students' interest and interest in actively participating in learning. The results of this study can strengthen and summarize previous findings regarding the Assure learning model. The findings have implications for teachers, namely that they can be taken into consideration in choosing the right learning model to increase student motivation in learning and support the learning process effectively and efficiently, namely by implementing the Assure model.